Pengembangan Media Karikatur Berbasis Kearifan Lokal Kediri bagi Siswa Sekolah Dasar - Daryanti, Eka Wahyu; Laila, Alfi; Saidah, Karimatus (Efektor, 2022)
The aims of this study were to: (1) determine the validity of Kediri local wisdom-based caricature media for elementary school students. (2) know the effectiveness of Kediri local wisdom-based caricature media for elementary school students. This research used R & D including five stages: analysis, design, development, implementation, and evaluation. The technique of collecting data used questionnaire validated by media expert, material expert, as well as limited and wide test. The technique of data analysis used the validity and effectiveness test (Sugiyono, 2012). The results of the research were: 1) Caricature media based on Kediri local wisdom obtained a validity score of 90% from media experts and 92% for material experts. 2) Caricature media based on Kediri local wisdom was categorized very effective, it can be seen that pre-test was 59.95 and post-test was 79.1. The results of limited and wide homogeneity were 0.049 > 0.005 and 0.948 > 0.005 (homogeneous data), while limited and wide normality test were 0.200 > 0.005 (normal data), paired T- test of limited and wide were 0.007 < 0.05 and 0.000 < 0.05, so there is an influence significant between pre-test and post-test. The results of the research are needed as a basis for developing Indonesian language learning in elementary schools.